A Study on Transparent Type Envelope Material in Terms of Overall Thermal Transfer, Energy, and Economy for an Office Building Based on the Thai Building Energy Code - Pathomthat Chiradeja; Surakit Thongsuk; Santipont Ananwattanaporn; Atthapol Ngaopitakkul; Suntiti Yoomak (My University, 2023)
Energy consumption in buildings has increased significantly as population and economic activities are concentrated in urban areas. Air conditioning accounts for a significant percentage of energy consumption in buildings, especially in tropical climates. The main area where heat can be transferred into the building is through glass windows. Thus, this study aims to evaluate feasibility in terms of overall thermal transfer value (OTTV), energy, and economics for retrofitting different glass materials in an office building in Thailand by using building energy code (BEC) software. The software uses Thailand’s building energy code as the standard to evaluate the energy performance of the case study building in comparison with different glass types used in retrofitted cases. From an economic perspective, the internal rate of return (IRR) and discounted payback periods (DPP) were used as determining indexes. The results demonstrated that retrofitted windows with the best energy-efficient glass might achieve energy performance, but installation cost can reduce economic feasibility, while the glass with the second lowest heat transfer coefficient can reduce the OTTV by 68.89% and building energy consumption by 16.87%. However, it can achieve the highest economic performance with 10.70% IRR and DPP at 11.83 years. Therefore, the balance between energy and economic factors must be considered to provide energy-efficient and investment-friendly glass materials for retrofit projects. In addition, the study focuses specifically on tropical climates. Thus, the finding may not be reflected similarly for buildings located in different regions.
Keywords: Retrofitting; Payback period; Building code; Investment; Consumption; Building envelope; Building Energy and Comfort Optimization